(Tl, Au)/Si(1 1 1)7×7 2D compound: an ordered array of identical Au clusters embedded in Tl matrix. (13th December 2017) - Mihalyuk, A N; Hsing, C R; Wei, C M; Eremeev, S V; Bondarenko, L V; Tupchaya, A Y; Gruznev, D V; Zotov, A V; Saranin, A A
Abstract: Formation of the highly-ordered 7 × 7 -periodicity 2D compound has been detected in the (Tl, Au)/Si(1 1 1) system as a result of Au deposition onto the Tl/Si(1 1 1) surface, its composition, structure and electronic properties have been characterized using scanning tunneling microscopy, angle-resolved photoelectron spectroscopy and density-functional-theory calculations. On the basis of these data, the structural model of the Tl–Au compound has been proposed, which adopts 12 Tl atoms and 10 Au atoms (in total, 22 atoms) per 7 × 7 unit cell, i.e. ̃1.71 ML of Tl and ̃1.43 ML of Au (in total, ̃3.14 ML). Qualitatively, the model can be visualized as consisting of truncated-pyramid-like Au clusters with a Tl atom on top, while the other Tl atoms form a double layer around the Au clusters. The (Tl, Au)/Si(1 1 1) 7 × 7 compound has been found to exhibit pronounced metallic properties at least down to temperatures as low as ̃25 K, which makes it a promising object for studying electrical transport phenomena in the 2D metallic systems.